The politics of Islamic identity in Southeast Asia - Islam, Syed Serajul (Thomson, 2005)
"The events of September 11, 2001 have made terrorism a burning topic. Consequently, separatist and revivalist movements in many parts of the world have been equated with terrorism. This book addresses the issue of terrorism, separatism and Islamic revivalism and examines, in minute detail, the movements in the Philippines, Indonesia, Thailand, Myanmar, and Malaysia. It is suitable as textbook for students majoring in Southeast Asian politics, and provides ample resources for researchers and experts on Southeast Asia."--pub. website desc.